Gastric Histopathological Image of Winstar Rats Induced by Ethanol After Red Ginger Extract Administration - Rohmani, Afiana; Shobri, Lilik Maula; Yazid, Noor; Purnamasari, Rina (Universitas Muhammadiyah Semarang, 2024)
Background: Alcohol can cause damage to the gastric mucosal barrier and reverse diffusion of HCL which results in damage to gastric tissue. The flavonoids in red ginger act as exogenous antioxidants which can ward off free radicals which reduce damage to the gastric mucosa caused by alcohol.Objective: To determine the differences in the histopathology of the rats gastric induced by 40% ethanol after administration of red ginger (Zingiber officinale var. rubrum) extract at graded doses.Methods: A post-test only group design method. 25 rats samples were divided into 5 groups: K(-) standard feed; K(+) ethanol 40% 1.8ml/200g/day; P1 red ginger extract 250mg/KgBW; P2 red ginger extract 500mg/KgBW; and P3 red ginger extract 750mg/KgBW. After 60 minutes, 40% ethanol was given at a dose of 1.8ml/200g/day. Treatment was carried out for 30 days, then on day 31 termination was carried out and gastric histopathology preparations were made with hematoxylin-eosin staining. Calculation of hull damage scores using the Barthel-Manja criteria. Analysis of differences in gastric mucosal damage between groups using the Kruskal Wallis Test and Mann Withney Test.Results: The difference between groups obtained significant results (p=0.003). There were significant differences between the K- and K+ groups (p=0.016), the K- and P1 groups (p=0.032), between the K- and P2 groups (p=0.032), between the K+ and P3 groups (p =0.032). Conclusion: Administration of red ginger extract at a dose of 750mg/KgBW was proven to be effective in preventing damage to the gastric mucosa induced by 40% ethanol.